RED-S: A review of the screening, diagnosis, treatment, and recovery - Matkin-Hussey, P. A.; Baker, D.; Ogilvie, M.; Beable, S.; Black, K. E. (Strength and Conditioning Journal, 2024)
Relative energy deficiency in sport (RED-S) is a complex syndrome of endocrine, metabolic, and physiological maladaptation. Adverse effects on physiological and psychological health and the performance of the athlete may occur due to a prolonged exposure to low-energy availability (LEA). LEA occurs when there is an energy intake (EI) deficiency relative to exercise energy expenditure (EEE) and normal physiological functioning. Early detection of the state of LEA and RED-S is crucial to prevent long-term negative health consequences. Given that LEA is the underlying cause of RED-S, increasing the athlete's energy availability (EA) to an optimal level is the recommended treatment. This paper reviews the current evidence and recommendations for the screening and diagnostic tools of LEA and RED-S, the recommended treatment strategies including reducing EEE, increasing EI, carbohydrate availability, within-day EA, psychological support, and the multidisciplinary team's role, and finally, it reviews the literature on its recovery process. It aims to provide a comprehensive summary of the research to date, with practical recommendations for the identification, management, and treatment of RED-S.